REVIEW OF CUSTOMARY DIVORCE IN MANIPI VILLAGE, PANA DISTRICT, MAMASA DISTRICT - Hidayah, Nur; Idrus, Wahyuni; Putri, Andi Istiana Inayah Dwi (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Divorce in Manipi Village, Pana District, Mamasa Regency still uses customary Law. Mamasa is where there is no need to bring a divorce suit to court, but it can be carried out according to custom; apart from that, there are also customary sanctions for perpetrators of divorce. This writing uses nonmatof research with a statutory and conceptual approach. Divorce according to custom in Manipi Village, Pana Subdistrict, Mamasa Regency, namely through customary judges and the local government, and giving Mamasa customary divorce sanctions (Kapaa) based on Tana' (caste) where the customary sanctions are in the form of buffalo and pigs, but due to developments the times, the payment of Kapaa at this time is by the agreement of the family in a case in the form of money or anything that costs a pig or buffalo.